Personnel costs and labour productivity: The case of European manufacturing industry - Alina Stundziene; Asta Baliute (Economies, 2022)
The objective of the article is to evaluate the impact of personnel costs on apparent labour productivity by employing the 1995-2018 panel data of the manufacturing industry in 27 European countries. The methods of independent samples t-test, correlation analysis, Granger causality test, unit root test, and ARDL were employed. The analysis shows that a long-term relationship exists among personnel costs and apparent labour productivity, and there are not significant differences among European countries concerning the impact of personnel costs on apparent labour productivity, but it varies in time. Companies often avoid increasing wages, as it decreases the profit of the company, and seek to increase the turnover in order to reduce the cost of goods sold. This research shows that growth of personnel costs does not necessarily mean lower profitability. The growth of personnel costs increases the gross operating rate if the turnover per person employed is stable. Turnover growth has a positive effect on apparent labour productivity, but a negative impact on the gross operating rate. Thus, the impact of turnover on apparent labour productivity is significantly lower than the impact of personnel costs on apparent labour productivity.
Keywords: 330; labour productivity; manufacturing industry; personnel costs; wages